1980
DOI: 10.1016/s0006-3495(80)84931-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a DNA unwinding protein and its complexes with oligodeoxynucleotides by x-ray diffraction

Abstract: The structure of the gene 5 DNA unwinding protein from bacteriophage fd has been solved to 2.3 A resolution by x-ray diffraction techniques. The molecule contains an extensive cleft region that we have identified as the DNA binding site on the basis of the residues that comprise its surface. The interior of the groove has a rather large number of basic amino acid residues that serve to draw the polynucleotide backbone into the cleft. Arrayed along the external edges of the groove are a number of aromatic amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
2
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
4
24
2
1
Order By: Relevance
“…From X-ray diffraction data [20] it was concluded that 2 lysyl residues (24 and 26) and 3 arginyl residues (21,80 and 82) may be situated at the inner surface of the DNA binding groove. In [21 ] DNA binding was inhibited upon acetylation of the lysyl residues.…”
Section: Discussionmentioning
confidence: 99%
“…From X-ray diffraction data [20] it was concluded that 2 lysyl residues (24 and 26) and 3 arginyl residues (21,80 and 82) may be situated at the inner surface of the DNA binding groove. In [21 ] DNA binding was inhibited upon acetylation of the lysyl residues.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregates were shown to be not present in the absence of nucleic acid. It has also been found that when gene 5 protein is combined with oligomers of four to eight in length, essentially irrespective of sequence, and subsequently crystallized, that these crystals invariably contain an aggregate of twelve gene 5 monomers as their asymmetric unit (11). These are in addition to the obvious and direct observation that in the presence of linear single stranded DNA contiguous aggregates appear and in its absence they do not.…”
Section: Rationale and Analysismentioning
confidence: 92%
“…The structural mechanism for these attractive interactions must be assumed absent or inoperative when no DNA is at hand, for the protein does not spontaneously aggregate in solution even at high concentrations but exists only as a discrete dimer specie. Thus linear strands of DNA must play a direct role in the cooperative phenomena, and indeed it appears that even short fragments of DNA, such as oligonucleotides, may also promote aggregate formation ( 10,11 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is nevertheless interesting to note the similarity between the predicted secondary structure of the central, RNA-binding domain of SI and the secondary structure of phage fd gene-5 protein (a small DNA-binding and unwinding protein whole structure has been determined at 0.23 nm resolution [64], composed entirely of antiparallel p-structure). Gene-5 protein contains two identical DNA-binding sites (of opposite orientations) in the diineric native state [64]. By analogy, it is tempting to speculate that the two homologous stretches in the central region of SI are involved in the RNA-binding and helix-destabilizing functions of this protein.…”
Section: Stwnrlury Structure Pvedictioiismentioning
confidence: 97%